The psychological wellbeing, ways of coping and religious coping among South African Muslims during the 2020 COVID-19 pandemic - Gani, Salma (My University, 2021)
The current COVID-19 pandemic brings to the fore the primary psychological concerns around elevated levels of stress and anxiety. Stressors include the fear of falling ill, financial woes due to not being at work, feeling powerless and the fear of potentially infecting others. Lifestyle changes such as limited social interaction and not being at work can result in feelings of isolation which can exacerbate anxiety and depressive symptoms. Coping styles during the lockdown may assist in promoting better wellbeing or decreasing wellbeing and if explored can aid with intervention for individuals. Religious coping in particular is often cited in conditions similar to COVID-19 wherein religious adherents view these circumstances as the will of God. With the noticeable psychological impact of COVID-19 it is necessary to understand the coping strategies employed under these circumstances and the effect on psychological wellbeing and understand the role of religious coping in particular, during times of uncertainty and distress. Therefore, this study sought to explore the relationships between coping and psychological wellbeing, and religious coping and psychological wellbeing in a sample of Muslim participants in South Africa during COVID-19. A total of 410 Muslim participants across South Africa completed a survey measuring coping styles, religious coping styles and psychological wellbeing during the COVID-19 lockdown period in South Africa. The results indicate that Muslims make use of acceptance and religious coping styles that can be attributed to their religious system of belief and practices. These were also correlated to their psychological wellbeing, suggesting that these coping strategies and religious coping strategies in particular have positive outcomes for wellbeing. Active coping and emotional support predict overall psychological wellbeing in this sample. This indicates that actively trying to cope with stressors associated with COVID-19 and turning to others for emotional support during this time to be useful coping strategies in promoting psychological wellbeing among South African Muslims. Future research can probe into the relationship between coping and different structures of wellness such as subjective wellbeing among South Africans during COVID-19. The result of this study adds to the growing body of literature surrounding COVID-19 in South Africa, and in particular culturally specific minorities which can help inform on therapeutic practices relevant to this new phenomena.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and research report in Social and Psychological Research to the Faculty of Humanities, University of the Witwatersrand, 2021